Systematic Literature Review: Analysis of Determinants of The Quality of BRT Transportation using The Kaizen Method - Haryadi Sarjono; Yuliana Tri Wulandari (Bina Nusantara University, 2022)
Transportation comes from the Latin word tranportare, and has 2 utilities, namely place utility and time utility to facilitate relationships between other communities. Article searches are carried out using the